2016
DOI: 10.21608/jkom.2016.109344
|View full text |Cite
|
Sign up to set email alerts
|

Uses and Gratifications of Selfie photos and its Relationship with Self-Objectification, Self-Esteem and Personality Traits among Adolescents

Abstract: Background: selfie capture phenomenon is one of recently discussed issues, which attract much of different categories of persons especially adolescents. Previous researches correlated it with narcissistic behaviors and feeling of inadequacy. Aim: to explore the relationship between adolescents' uses of selfie photos and their self objectification and self esteem levels as well as their personality traits. Methods: A total number of 1432 adolescent students from preparatory (N= 274), secondary (N= 193) and univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
1
0
1
Order By: Relevance
“…This might be because men have been observed to be more intrepid and daring in their social presentation and expression across cultures and academic studies. These study findings are consistent with those conducted in Egypt found that males are more likely than females to post selfie photos on social media [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This might be because men have been observed to be more intrepid and daring in their social presentation and expression across cultures and academic studies. These study findings are consistent with those conducted in Egypt found that males are more likely than females to post selfie photos on social media [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…These study results agreed with previous study found that students may view selfies as pointless, awkward, and uncool; further, they believe it is an attention-seeking activity [ 34 ]. However, this finding contradicts a study published in Egypt, which found that male students have more negative attitudes regarding selfies [ 35 ].…”
Section: Discussioncontrasting
confidence: 91%